Privacy and Biometric Passports - Ioannis Vakalis (The Scientific World Journal)
This work deals with privacy implications and threats that can emerge with the large-scale use of electronic biometric documents, such the recently introduced electronic passport (e-Passport). A brief introduction to privacy and personal data protection is followed by a presentation of the technical characteristics of the e-Passport. The description includes the digital data structure, and the communication and reading mechanisms of the e-Passport, indicating the possible points and methods of attack.